Indicadores de desempenho logístico: uma abordagem para serviços de transportes - Laurindo, Hildeanne Andrade (2009)
This work shows the importance of the evaluation in the logistics indicators for the increase of the quality in services of transports of loads and orders. This dissertation seeks to identify opportunities of improvement of the quality of the services rendered by companies of transports starting from the evaluation of the indicators of logistics acting. Quality, more and more exalted in commercial negotiations that result in the customer's satisfaction, became a competitive diferencial of the organizations, what is not different in the segment of logistics marketing. Logistics embraces several activities that assist the flow of products given to the final consumer, involving from the movement and raw material storage to final product. However, among a lot of logistics activities, this research gives a great importance to the transporting activity, a lot of times confused with logistics itself, even because of its importance in the economy of any country. A study of case of a transport company will be showed in this work. When we evaluate a transport company, we obtain the possibility to know as the same it uses of the tool of the quality to offer better services for the customers. However, that is only possible for the big it was worth of the literary revision also presented on the logistics acting and the analysis of the found models of measure logistics, to evaluate also and scientifically the model used by the organization in focus. Through field rising, the analysis of the results was observed reached by the company, as well as of its main branch and, in that way the maximum of information was gotten, besides of the confrontation of actings, to certify it that in fact the acting indicators can join from value to the quality noticed in the services of presented transports. It was verified that through the focus in the important indicators is possible to identify the restrictive factors that deserve special attention to improve the acting and still to pick up improvement contributions in the services.